1993
DOI: 10.1002/pro.5560021203
|View full text |Cite
|
Sign up to set email alerts
|

Sequence‐specific

Abstract: CD59 is a recently discovered cell-surface glycoprotein that restricts lysis by homologous complement and has limited sequence similarity to snake venom neurotoxins. This paper describes the first results of a two-dimensional NMR study of CD59 prepared from human urine. Nearly complete 'H-NMR assignments were obtained for the 77 amino acid residues and partial assignments for the N-glycan and the glycosylphosphatidylinositol (GPI) anchor. These results together confirm that the C-terminal residue of the mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Recently, the disulfide bond connectivity of the NH2-terminal domain of uPAR has been solved (Ploug et al, 1993) and has been found to be homologous to that of the nonglycosylated snake venom a-neurotoxins, suggesting that the individual uPAR domains adopt the same overall structural topology as these toxins. Recent 'H-NMR assignments for MIRL/CD59 are consistent with a model in which this protein, homologous to the uPAR domains, has a gross folding topology similar to that of the snake a-neurotoxins (Fletcher et al, 1993).…”
mentioning
confidence: 83%
“…Recently, the disulfide bond connectivity of the NH2-terminal domain of uPAR has been solved (Ploug et al, 1993) and has been found to be homologous to that of the nonglycosylated snake venom a-neurotoxins, suggesting that the individual uPAR domains adopt the same overall structural topology as these toxins. Recent 'H-NMR assignments for MIRL/CD59 are consistent with a model in which this protein, homologous to the uPAR domains, has a gross folding topology similar to that of the snake a-neurotoxins (Fletcher et al, 1993).…”
mentioning
confidence: 83%
“…The amino acid sequence and solution structure of CD59 conform to those of the Ly6/cardiotoxin protein superfamily in which five internal disulfide bonds stabilize the polypeptide into a discoid structure consisting of a three-stranded ␤-sheet apposed to a two-stranded ␤-finger (14 -17). In CD59, the GPI anchor is attached to the C-terminal Asn 77 , and Asn 18 provides a single site of N-linked glycosylation (14,15,18). Whereas the carbohydrate attached to Asn 18 occludes most of one face of the discoid surface of the protein, these glycosidic residues do not contribute to the MAC inhibitory properties of CD59 (14, 15, 18 -20).…”
mentioning
confidence: 99%
“…Nevertheless, because the level of cell surface expression of each recombinant protein (mutant or wild type) was not reported, these data do not permit definitive conclusion as to the relative MAC inhibitory function of the Ser 20 3 Ala mutant. Furthermore, this study did not resolve whether this mutation resulted in glycosylation at CD59 residue Asn 8 , a second potential site for N-glycosylation that is normally not glycosylated in wild type CD59.…”
Section: Cd59 Glycosylationmentioning
confidence: 99%
“…Based upon sequence and solution structure, CD59 belongs to the snake venom/LY6 protein superfamily, whose members include cardiotoxins, erabutoxins, and the murine lymphocyte LY6 antigen (7)(8)(9). These proteins contain a characteristic disulfide-bonded polypeptide core comprised of a four-stranded ␤-sheet apposed to a two-strand ␤-finger.…”
mentioning
confidence: 99%
See 1 more Smart Citation